SCHOOL-BASED VIOLENCE AND PEACE: IMPROVING LEARNING IN HIGHER EDUCATION AMONG ADULT SURVIVORS OF SCHOOL BULLYING - Jonathan Chukwuemeka Madu; Abugu Solomon Ogbonna (International Studies Journal)
Promoting equity and egalitarian society is very vital for enhancing human development, and one of the most powerful instruments for this purpose is education, which boosts people’s self-confidence, equips them for their future; to act responsibly in making better choices and relevant contributions in their society. Evidence exists of considerable problems with bullying and bullied children in secondary schools that undermine these efforts as a result of their long-lasting effects for the victims, which include hindrance in learning and advantages of higher education in their survivors. The psychological damage and pain caused by bullying can become almost indelible and affect one’s future. This article using 40 undergraduate students of Michael Okpara university of Agriculture, Umudike and 112 students from two secondary schools, (Nigeria), examines the effects of secondary school bullying on their tertiary education, and the effectiveness of peer-mediation as early intervention. The sample was purposively selected from four colleges in the university. The study indicates that bullying experienced in secondary school could adversely affect the self-esteem and performance of the survivors at tertiary education level and importance of earlier intervention to improve learning.